(untitled) (Bangladesh Journal of Infectious Diseases, 2022)
As the current global pandemic of the novel coronavirus diseases 2019 (COVID-19) continues to rage, the scientific and medical worlds are working to establish an effective therapy against the illness. Recently questions regarding non-steroidal anti-inflammatory drugs (NSAIDs) as a potential therapeutic option for COVID-19 have surfaced. While some studies hint towards the possible benefit of NSAIDs against SARS-CoV-2 infection, the current body of evidence also sheds light on the potential risk of using NSAIDs in COVID-19 patients. Thus, the available literature does not provide conclusive evidence for or against the use of NSAIDs for treating COVID-19 patients. Given the limited data available, we suggest cautionary approaches for the public to avoid possible harm until further evidence emerges. NSAIDs should not be used as the first-line agents for COVID-19 unlessunder medical supervision. Moreover, patients with chronic inflammatory conditions should continue the NSAIDs as per their regular prescriptions. Bangladesh Journal of Infectious Diseases 2021;8(1): 50-52